RESERVATION SYSTEM FOR THE SUPPLY OF GOODS CV. HIDUP BARU - Hasan Sutomo; Sunarto Usna, Drs (Jurnal Sistem Informasi, 2000)
System for ordering of goods is one of the activities of companies which have animportant role in increasing production for the company. In carrying out good roleordering system enables the company to exit the entry of the goods of the company. Ifcompanies do a good reservation system then the activities of the company'sproduction will go smoothly. Thus a system of reservations made goods.